Concise Review: Cancer Stem Cells and Minimal Residual Disease - Ghiaur, Gabriel (Stem Cells, 2012)
Evidence gathered over the past two decades confirms earlier reports that suggested that hematologic malignancies exhibit a hierarchical differentiation structure similar to normal hematopoiesis. There is growing evidence that some solid tumors may also exhibit a differentiation program similar to the normal tissue of origin. Many excellent reviews on the topic of cancer stem cells (CSCs) document the recent explosion of information in the field, particularly highlighting the phenotypic and functional characteristics of these putative cells in vitro. Accordingly, here we only briefly discuss these concepts, and instead primarily examine the potential clinical relevance of CSCs, arguably the major unresolved issue in the field. Although it is generally accepted that CSCs are resistant to chemotherapy in vitro, only recently have data surfaced that suggest a role for these cells in disease relapse. Importantly, cancer cells with a stem cell phenotype have been found to be enriched in minimal residual disease of several malignancies. If the role of CSCs in relapse is confirmed, targeting these cells would hold substantial potential for improving the outcome of cancer patients.